Effects of physicochemical factors on seasonal variations of phytoplankton in the Mond River Estuary of Bushehr Province, Persian Gulf, Iran - MOJTABA POULADI; AMIR QADERMARZI; FATEMEH BAHARVAND; AMIR VAZIRIZADEH; ALIAKBAR HEDAYAT (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Pouladi M, Qadermarzi A, Baharvand F, VazirizadehA, Hedayati A. 2017. Effects of physicochemical factors on seasonal variations of phytoplankton in the Mond River Estuary of Bushehr Province, Persian Gulf, Iran. Biodiversitas 18: 229-237. The main purpose of present study was to investigate the abundance and biodiversity of phytoplankton from Mond estuary, Bushehr, Persian Gulf during different seasons and its relationships with environmental parameters and nutrients. Samples were taken in mid-season from spring 2012 to winter 2013 for oneyear period. The phytoplankton were contributed by the phyla Bacillariophyta, Dinophyta, Haptophyta, and Chlorophyta. The class Coscinodiscophyceae and Bacillariophyceae belonging to Bacillariophyta were the most diverse and dominant with 22 and 16 genera, respectively. The mean phytoplankton abundance were recorded in spring (12706.7±3586.9 cells L-1), in summer (10173.3±2560.08 cells L-1), in autumn (10600±2758.2 cells L-1) and in winter (7000±2401.6 cells L-1), respectively. Simpson and Shannon-Wiener biodiversity indices obtained showed in spring (0.93±0.007 and 3.8±0.2), in summer (0.92±0.008 and 3.64±0.2), in autumn (0.92±0.006 and 3.63±0.15) and in winter (0.89±0.013 and 3.07±0.24), respectively. The phytoplankton assemblages were most diverse and abundant at station-5 in all seasons. In addition, there were significant correlation (P<0.01) between phytoplankton abundance and diversity with pH, salinity, NO3, PO4 and temperature. Based on Principle Component Analysis (PCA), the most important factors that could describe most changes of abundance and diversity of phytoplankton in the Mond River estuary system were salinity, NO3, pH, PO4 and temperature, respectively. Results demonstrated that diatoms were the dominant population and salinity factor was more effective factor that affected the diversity and abundance of phytoplankton during study period in Mond River estuary. Keywords: Abundance, Bushehr, diversity, Mond River Estuary, phytoplankton, Persian Gulf